2018
DOI: 10.1007/s11273-018-9635-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multi-decadal wetland changes, and cumulative impact of multiple storms 1984 to 2017

Abstract: Land-cover classification analysis using Landsat satellite imagery acquired between 1984 and 2017 quantified short-(post-Hurricane Sandy) and long-term wetland-change trends along the Maryland and Virginia coasts between Metompkin Bay, VA and Ocean City, MD. Although there are limited options for upland migration of wetlands in the study area, regression analysis showed that wetland area increased slightly between 1984 and 2011, indicating that marsh aggradation rates were sufficient to maintain wetland elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Compared with the use of static thresholds [37,81,82,84], dynamic histogram thresholds reduce classification uncertainties stemming from spectral variability related to changes in instrumentation and/or differences in atmospheric or seasonally-variable hydrologic and phenologic conditions between acquisition dates [95,96]. Further, the methods described here allow for rapid classification and delineation of barrier-island extents from a large number of source images relative to more time-consuming object-based [39,97], supervised [38], and unsupervised [35] classification techniques, which require training data to guide the classification and (or) "expert knowledge" to group similar clusters. Our resulting multi-decadal, high temporal resolution dataset provides a basis for better understanding the timing, nature, and potential drivers of landscape change [98] compared with assessments that quantify discrete changes between just a few points in time [38,39,91].…”
Section: Automatic Thresholding Of Mulitple Spectral Indices For Rapi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the use of static thresholds [37,81,82,84], dynamic histogram thresholds reduce classification uncertainties stemming from spectral variability related to changes in instrumentation and/or differences in atmospheric or seasonally-variable hydrologic and phenologic conditions between acquisition dates [95,96]. Further, the methods described here allow for rapid classification and delineation of barrier-island extents from a large number of source images relative to more time-consuming object-based [39,97], supervised [38], and unsupervised [35] classification techniques, which require training data to guide the classification and (or) "expert knowledge" to group similar clusters. Our resulting multi-decadal, high temporal resolution dataset provides a basis for better understanding the timing, nature, and potential drivers of landscape change [98] compared with assessments that quantify discrete changes between just a few points in time [38,39,91].…”
Section: Automatic Thresholding Of Mulitple Spectral Indices For Rapi...mentioning
confidence: 99%
“…These studies often emphasize short-term changes induced by extreme storm events [14,15,23,[27][28][29] and most consider the sandy barrier-island (beach and dune) and back-barrier (marsh and tidal flat) environments separately. Recent studies, however, demonstrated the importance of whole-system connectivity to barrier morphology and evolution [30][31][32] and expanded the scope of historical analyses to consider the annual-to decadal-scale landscape evolution of barrier islands [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These damages, combined with the stress caused by the increased soil salinity, can lead to mortality of the stressed stand [66,71,89]. The repercussions of these storm events increase dramatically if more than one storm occurs in successive years [90].…”
Section: Soil Salinity and Severe Stormsmentioning
confidence: 99%
“…Although remote sensing offers a way to assess and monitor large-scale changes in vegetation following storm events (e.g. Carter et al, 2018;Douglas et al, 2018;Stagg et al, 2020), elucidating how saltwater flooding, mechanical damage, litter accumulation and sediments affect the plant community is challenging. There is, however, a relatively large body of research describing the (species-specific) effects of burial by sediments on sand dune species (Sykes and Wilson, 1988;Harris et al, 2017; High mortality of Floridian 'freshwater forest' species.…”
Section: Supra-tidal Plant Communitiesmentioning
confidence: 99%